The impact of visual content from drones on the behavior of potential customers in the field of hotel marketing - Kotova, Olha (Актуальні питання економічних наук, 2025)
The hospitality industry is undergoing profound transformations related to the development of digital technologies, changing consumer behavioral patterns, and growing requirements for personalization of marketing communications. In this context, the role of visual content as a means of creating an emotional connection with the client at the stage of familiarization with the service is growing. The purpose of the study is to determine the impact of visual content created with the help of drones on the behavior of potential customers in the field of hotel marketing, as well as to assess its effectiveness as a tool for stimulating demand and emotional engagement of consumers. Methods.The study uses an interdisciplinary approach, which includes the analysis of scientific sources, generalization of practical experience in the implementation of visual content in digital marketing of hotels, structural and logical modeling of the impact of drone video on customer behavior, as well as content analysis of digital promotion channels (social networks, booking platforms, websites, etc.). Results. It has been established that videos from drones activate the emotional perception of the offer, build trust, and create a positive brand image. The advantages and challenges of introducing drone technologies in the hospitality field are systematized. Digital channels of marketing communication in the hotel business are analyzed; the key elements of visual content from drones in hotel marketing have been identified; the psychological and communication effects that drone content causes in consumers and the behavioral reactions of potential customers to drone videos have been studied; strategic approaches to the use of drones in hotel marketing have been studied; A model of the influence of video from drones on customer behavior is proposed. Conclusions. Visual content from drones is a practical element of hotel marketing, which significantly changes approaches to promoting and consuming hotel services. Further implementation of such solutions requires the integration of digital competencies in the professional training of marketers, adapting strategies to the target audience, and using creative methods of personalized content. The scripted approach to the video and the technical characteristics of the device determine the effectiveness of drone visual content. The integration of high-tech equipment will create a competitive video product that enhances the marketing impact on different target audience segments. This opens up new opportunities for building an image, building trust, and stimulating action, particularly booking.